The effect of sleep quality on cognitive functions among young adult in UiTM Seremban 3 / Nurun Naja ... [et al.]. - Naja, Nurun; Najihah, Nur; Sahira, Naimi; Taufiq, Muhammad; Akif, Muhammad; Syed Mud Puad, Sharifah Maimunah (2024)
Both physiological and psychological processes are improved by having good sleep quality. Though good sleep is crucial, young people frequently struggle with it as a result of the modern lifestyle. The objective of this study is to identify the sleep quality, level of cognitive function and whether sleep quality influences cognitive functions among young adults in UiTM Seremban 3. A total of 27 students from UiTM Seremban 3 were selected, and the data were collected over 7 days using protocol testing by [3] Accelerometers were used to assess participants’ sleep quality, while N-Back tasks for working memory and Wisconsin Card Sorting Test (WCST) for executive function were used to assess the cognitive function of participants. Linear regression was used to analyse the correlation between sleep quality, working memory, and executive function. Reports from 26 young adults in UiTM Seremban 3 (22.3 ± 1.04 years) indicate a higher prevalence of moderate sleep quality (6.13 ± 1.044) and cognitive function for N-Back Test (78.3 ± 4.22) and WCST (-0.236 ± 0.4559). The findings show that the correlation between sleep quality and working memory is a significant correlation (β = 0.540; p = 0.030), while the correlation between sleep quality and executive function shows no significant correlation (β = 0.120; p = 0.097). These findings demonstrated sufficient evidence that sleep quality affects working memory (p < 0.05) but not executive function. Hence, sleep quality is associated with better cognitive performance of working memory in young adults.